STUDY OF WAVE HEIGHT POTENTIAL FOR DETERMINING THE LOCATION OF WECS IN THE WATERS OF KETAPANG REGENCY BY USING CEDAS SOFTWARE - Suratman, Teguh; Danial, Mochammad Meddy; Lestari, Arfena Deah; Meirany, Jasisca; Supriyadi, Asep (Jurnal Teknik Sipil, 2023)
Ketapang Regency's increasing demand for electrical energy could lead to an energy crisis. According to these issues, the Sungai Kinjil and Kinjil Pesisir coastal communities in the Ketapang Regency have wave potential that can be used as energy for marine wave power plants. As a result, The expertise required to evaluate ocean wave resources and determine the output power of electrical energy produced by ocean waves. CEDAS and ArcGIS software is used for wave modeling, with CEDAS input data in the form of wave forecasting from BMKG wind data, bathymetry, and coastline data obtained from the official Indonesia Geospatial website, and primary data in the form of wave electric power measurement data obtained from Wave energy conversion system prototypes. CEDAS processing results show the highest wave height of 0,998 meters at a depth of 1,3 meters. The potential for electrical energy at the research site is 1,908"“4,512 kw/m2.